Creation of Centimeter‐Sized 2 D Crystalline Film by Crystallization of Homopolymer in Solution. Issue 61 (9th October 2018) - Li, Ming; Peng, Zefei; Hou, Jingjing; Liu, Xiong; He, Yunbin
Abstract: The 2 D assembly of polymers to form free‐standing and large crystalline films is quite appealing but very challenging. Although there have been some works using interface templates, reports of in situ assembly in solution are still rare. Herein, a simple strategy is developed for the creation of a free‐standing and centimeter‐sized 2 D crystalline polymer film through crystallization of an amphiphilic brush polydiacetylene (PDA) in solution. The film exhibits good shape memory, a low dielectric constant, and good carrier mobility. This strategy may be applied extensively to produce a variety of other macroscopic 2 D crystalline polymer films for applications in electronics, catalysis, and so on. Abstract : Crystallizing polymers : An amphiphilic brush polydiacetylene is crystallized in solution, yielding a free‐standing and centimeter‐sized 2 D crystalline polymer film (see figure), which exhibits good flexibility, shape‐memory properties, an ultra‐low dielectric constant, and good carrier mobility.